A Single‐Dot Perovskite Spectrometer. Issue 33 (7th July 2022) - Guo, Linqi; Sun, Haoxuan; Wang, Min; Wang, Meng; Min, Liangliang; Cao, Fengren; Tian, Wei; Li, Liang
Abstract: There are significant applications for miniature on‐chip spectrometers in many fields. However, at present, on‐chip spectrometers have to utilize an integrated strategy to achieve spectral analysis, which undoubtedly squanders the photosensitive area and adds pressure to the miniaturization of the spectrometer. Here, a unique spectrometer design that adopts a single detection point with in situ modulation realized by the photogain control at various bias voltages is demonstrated. With micrometer‐level footprints, this single‐dot spectrometer processes a resolution of about 5 nm and a response time down to about 197 µs. This is the first in situ perovskite modulation strategy that breaks the footprint‐resolution restriction of spectrum analysis and demonstrates a new design direction for functional perovskite devices. Abstract : A single‐dot perovskite spectrometer is demonstrated, which first breaks the long‐standing restriction of footprint‐resolution. The control of ion migration in the perovskite is the key of the spectrum richness and cyclic stability. Without any optical and mechanical structure, the spectrum can be recognized by a single detector through the bias stimulated photogain modulation.